What Is the Link between Stringent Response, Endoribonuclease Encoding Type II Toxin–Antitoxin Systems and Persistence? - Ramisetty, Bhaskar C. M.; Ghosh, Dimpy; Roy Chowdhury, Maoumita; Santhosh, Ramachandran S. (Frontiers in Microbiology, 2016)
Persistence is a transient and non-inheritable tolerance to antibiotics by a small fraction of a bacterial population. One of the proposed determinants of bacterial persistence is toxin-antitoxin systems (TAS) which are also implicated in a wide range of stress-related phenomena. Maisonneuve E, Castro-Camargo M, Gerdes K. 2013. Cell 154:1140-1150 reported an interesting link between ppGpp mediated stringent response, TAS, and persistence. It is proposed that accumulation of ppGpp enhances the accumulation of inorganic polyphosphate which modulates Lon protease to degrade antitoxins. The decrease in the concentration of antitoxins supposedly activated the toxin to increase in the number of persisters during antibiotic treatment. In this study, we show that inorganic polyphosphate is not required for transcriptional activation of yefM/yoeB TAS, which is an indirect indication of Lon-dependent degradation of YefM antitoxin. The Δ10 strain, an Escherichia coli MG1655 derivative in which the ten TAS are deleted, is more sensitive to ciprofloxacin compared to wild-type MG1655. Furthermore, we show that the Δ10 strain has relatively lower fitness compared to the wild type and hence, we argue that the persistence related implications based on Δ10 strain are void. We conclude that the transcriptional regulation and endoribonuclease activity of YefM/YoeB TAS is independent of ppGpp and inorganic polyphosphate. Therefore we urge for thorough inspection and debate on the link between chromosomal endoribonuclease TAS and persistence.